The Red Army. Ed. by Major-General Fomichenko [Fomičenko] (Hutchinson)
With appendix: J.V. Stalin. [ps. of Iosif Vissarionovič Džugašvili]. Report on the 27th anniversary of the Great October Socialist Revolution.